The Utilization of Virtual Reality (VR) of Islamic Historical Sites to Enhance Contextual Understanding of Sababun Nuzul Hadiths - Fiqih Ananda; Ilda Putri; Indah Gayatri; Muhamad Yahya (Journal Emerging Technologies in Education, 2026)
Background. Understanding the historical context of Hadiths, particularly the Sababun Nuzul (circumstances surrounding the emergence and transmission of Hadiths), remains a significant challenge for students in Islamic studies. Conventional teaching methods often rely on textual descriptions that limit learners’ ability to visualize historical settings and events. Purpose. This study aimed to investigate the effectiveness of utilizing Virtual Reality (VR) representations of Islamic historical sites in enhancing students’ contextual understanding of Sababun Nuzul Hadiths. The study also explored students’ perceptions of VR-based learning as an educational tool in Islamic studies. Method. A quantitative research design was employed involving undergraduate students enrolled in Islamic studies courses. Participants experienced VR-based learning environments featuring reconstructed Islamic historical sites associated with selected Hadith narratives. Data were collected through contextual understanding tests and perception questionnaires and analyzed using descriptive and inferential statistical techniques. Results. The findings revealed that students who engaged with VR-based learning demonstrated significantly higher levels of contextual understanding compared to those who learned through conventional instructional approaches. The participants also reported positive perceptions regarding learning motivation, engagement, historical visualization, and knowledge retention. Conclusion. The integration of Virtual Reality into Islamic education provides an effective approach to improving students’ contextual understanding of Sababun Nuzul Hadiths. The immersive and interactive nature of VR facilitates meaningful learning experiences and supports the modernization of Islamic educational practices. Future studies are encouraged to explore the integration of both VR and AR technologies across broader areas of Islamic learning.